Alien species spreading via biofouling on recreational vessels in the Mediterranean Sea. Issue 12 (25th September 2019) - Ulman, Aylin; Ferrario, Jasmine; Forcada, Aitor; Seebens, Hanno; Arvanitidis, Christos; Occhipinti‐Ambrogi, Anna; Marchini, Agnese
Abstract: Despite the Mediterranean being both a hotspot for recreational boating and for non‐indigenous species (NIS), no data currently exists on the recreational boating sector's contribution to the spread of NIS in this Sea. To improve the basis for management decisions, a wide‐scale sampling study on the biofouling communities of recreational vessels and marinas was undertaken. Specifically, we surveyed over 600 boat owners and sampled the same boat hulls for NIS in 25 marinas across the Mediterranean, from France to Cyprus, to determine which factors (i.e. boat characteristics, travel behaviour, home marina) are associated with higher NIS richness on boat hulls. Among the surveyed boats, we found recreational vessels to travel considerably, averaging 67 travel days and 7.5 visited marinas per annum. This results in a high potential for spreading NIS, especially as 71% of sampled vessels host at least one (and up to 11) NIS. Boats with high NIS richness strongly correlate with home marinas with high NIS richness. Over half of the vessels were carriers of NIS which were not yet present in the marinas they were visiting. The presence of biofouling in niche areas of the hull (i.e. in the cavities and metallic parts) emerges as the best predictor for NIS richness on boats, along with longer times since their last cleaning and antifouling applications. Interestingly, colonization of NIS occurred rapidly, even on boats that had recently had their hulls cleaned professionally. Synthesis and applications . We demonstrate that recreational boating has a very high capacity for the spread of non‐indigenous species (NIS) in the Mediterranean, due to both high NIS richness on boats and extensive travel. To counteract the spread of NIS, routine monitoring for new NIS needs to be established for both marinas and vessels, along with frequent pontoon cleaning. Additionally, policy should require preliminary screenings for incoming vessels from new countries, especially those emanating from high‐risk marinas. The niche areas of the boat hulls should be checked first for biofouling, which was the best predictor for NIS richness since they often go overlooked with in‐water cleanings are rarely have antifouling applied to them. Abstract : We demonstrate that recreational boating has a very high capacity for the spread of non‐indigenous species (NIS) in the Mediterranean, due to both high NIS richness on boats and extensive travel. To counteract the spread of NIS, routine monitoring for new NIS needs to be established for both marinas and vessels, along with frequent pontoon cleaning. Additionally, policy should require preliminary screenings for incoming vessels from new countries, especially those emanating from high‐risk marinas. The niche areas of the boat hulls should be checked first for biofouling, which was the best predictor for NIS richness since they often go overlooked with in‐water cleanings are rarely have antifouling applied to them.